Tuning of the electrochemical properties of transparent fluorine-doped tin oxide electrodes by microwave pulsed-plasma polymerized allylamine. (1st August 2019) - Cirocka, Anna; Zarzeczańska, Dorota; Wcisło, Anna; Ryl, Jacek; Bogdanowicz, Robert; Finke, Birgit; Ossowski, Tadeusz
Abstract: We report here the dry, one-step, and low-temperature modification of FTO surfaces using pulsed plasma polymerization of allylamine (PPAAm). PPAAm/FTO surfaces were characterized by X-ray photoelectron spectroscopy, spectroscopic ellipsometry, and contact angles to understand the morphological, structural, and optical properties. FTO were coated with a very thin layer of adherent cross-linked, pinhole-, and additive-free allylamine plasma polymer resistant to hydrolysis and delamination, and characterized by a high density of positively charged amino groups. Electrochemical studies revealed that PPAAm/FTO electrodes show wide range pH stability and reaction rates tuned by the duration of plasma treatment. We show how the modification of plasma treatment duration between 72 s and 288 s affects the chemical structure and thickness of the obtained modification, having a strong influence on the charge transfer kinetics. In particular, XPS revealed the occurrence of the reduction processes under long-term plasma exposure proving the need for monitoring of this key factor. This covalent immobilization of amine compounds on FTO surface using rapid process in microwave pulsed-plasma makes it a promising electrode for future applications in electrochemical biosensors and optoelectronic devices. Graphical abstract: Image 107171